Synergistic Effects of Surface Coating and Bulk Doping in Ni‐Rich Lithium Nickel Cobalt Manganese Oxide Cathode Materials for High‐Energy Lithium‐Ion Batteries. Issue 4 (31st January 2022) - Reissig, Friederike; Lange, Martin A.; Haneke, Lukas; Placke, Tobias; Zeier, Wolfgang G.; Winter, Martin; Schmuch, Richard; Gomez‐Martin, Aurora
Abstract: Invited for this month′s cover is a combined work of the Helmholtz Institute Münster together with the MEET Battery Research Center and the Universities of Münster and Mainz. The cover shows multiple treatment choices for the modification of cathode active materials for lithium‐ion batteries. Similar to a car wash program, the treatment will typically result in an improvement of the status quo. However, the best treatment procedure will only become clear if all modification pathways are explored. The Research Article itself is available at 10.1002/cssc.202102220 . Abstract : "…the concurrent combination of such approaches is not as trivial as one might expect." This and more about the story behind the research that inspired the Cover image is presented in the Cover Profile. Read the full text of the corresponding research at 10.1002/cssc.202102220 . View the Front Cover here: 10.1002/cssc.202200079 .